Photo-thermal conversion double-layer composite phase change material and preparation method thereof

By adopting a double-layer composite structure of expanded graphite and carbon nanotubes in the photothermal conversion phase change material, the problem of inadequate utilization of photothermal materials in traditional photothermal conversion materials is solved, and efficient photothermal conversion and storage are achieved.

CN119505822APending Publication Date: 2025-02-25ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411663181.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

In actual use of traditional photothermal conversion phase change materials, photothermal materials can only play a role on the structural surface, and the internal photothermal materials cannot come into contact with sunlight, resulting in waste of resources and inefficiency.

Method used

By mixing expanded graphite and carbon nanotubes at a certain mass ratio, a double-layer composite phase change material of the photothermal layer and the phase change heat storage layer is formed. The expanded graphite is used to closely combine the photothermal layer with the phase change layer to ensure that the photothermal material is fully utilized.

Benefits of technology

The full utilization of photothermal materials is achieved, the high photothermal conversion efficiency is maintained, the amount of photothermal materials is reduced, the preparation is simple, the process repeatability is good, and it is easy to industrialize.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505822A_ABST
    Figure CN119505822A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of photothermal conversion and composite phase change materials, and particularly relates to a photothermal conversion double-layer composite phase change material and a preparation method thereof.The preparation method comprises the following steps that expanded graphite and a carbon material are evenly mixed to obtain mixed powder; the composite phase change material powder is evenly spread in a pressing mold to serve as a lower layer, then the obtained mixed powder is spread on the composite phase change material powder and covers the whole surface, pressing forming is conducted, and a double-layer structure block with the upper layer being a photothermal conversion layer and the lower layer being a phase change heat storage layer is obtained; and treating the photothermal conversion layer to form a certain roughness, thereby obtaining the double-layer composite phase change material capable of photothermal conversion. The photo-thermal material and the phase change material are laminated, pressed and compounded, the photo-thermal material is fully utilized, the use amount of the photo-thermal material is effectively reduced while high photo-thermal conversion efficiency is kept, and the photo-thermal composite material is simple to prepare, good in process repeatability and easy to industrialize.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photothermal conversion and composite phase change materials, and in particular relates to a double-layer composite phase change material capable of photothermal conversion and a preparation method thereof. Background Art

[0002] Phase change thermal storage materials use their own phase changes to store energy. They have the advantages of high energy storage density and basically constant temperature when storing and releasing heat, and are widely studied in the field of thermal storage. In human society, the sources of energy used can ultimately be traced back to sunlight. Although the most commonly used form of energy is electricity, most of the electricity consumption is ultimately used to generate heat. Therefore, if sunlight can be directly converted into thermal energy and stored and utilized, it will have higher energy utilization efficiency, simpler conversion structure and lower cost than from light to electricity and then to heat. Phase change materials with photothermal conversion capabilities can not only perform photothermal conversion, but also store the generated heat in a timely and efficient manner. This is of great significance for further improving the conversion efficiency of sunlight, reducing the cost of sunlight utilization, and promoting the efficient use of solar energy.

[0003] Traditional solid-liquid phase change materials have poor ability to capture photons and cannot be used directly for photothermal conversion. Therefore, scholars usually choose to combine photothermal materials with shaped phase change materials to improve the overall photothermal conversion ability of phase change materials. At present, photothermal conversion phase change materials basically adopt the form of shaped uniform structure or microcapsules, that is, the photothermal conversion material and phase change material in the material are evenly dispersed with each other, forming a whole with uniform structure and composition, or the phase change material is completely coated and sealed with photothermal conversion material. After searching, the relevant prior art is as follows:

[0004] Lanzhou University of Technology composited carbonized pectin and attapulgite with dodecylamine to obtain a uniform structure composite phase change material with a phase change latent heat of 175.7 J / g and a photothermal conversion efficiency of 77.5% (Wang Linqiang, Preparation of stereotyped phase change composite materials and research on their photothermal energy storage performance, Master's thesis of Lanzhou University of Technology, 2022). Although this photothermal conversion phase change material with a uniform structure simplifies the material preparation process to a certain extent, in actual use, only the photothermal material on the surface of the structure plays a photothermal conversion role, and the photothermal material inside the material does not come into contact with sunlight and does not play a photothermal conversion role.

[0005] Beijing University of Chemical Technology uses Fe3O4 and CaCO3 to coat n-eicosane to form phase change microcapsules with photothermal conversion capabilities. The phase change latent heat is 107.2 J / g and the photothermal conversion efficiency is 86.4% (Tian Donglin, Preparation of magnetic phase change material microcapsules and research on their photothermal conversion applications, Master's thesis of Beijing University of Chemical Technology, 2023). The preparation process of this microcapsule is complicated and most microcapsules will not come into contact with sunlight for photothermal conversion, and the heat storage part cannot be expanded. All of these have caused a certain degree of waste of relatively high-cost photothermal materials. Directly pressing the photothermal material and the phase change material in layers will not form a tightly connected whole due to the differences in their properties (such as differences in thermal expansion coefficients, polarity, etc.), or they will quickly delaminate during use, resulting in a significant reduction in efficiency. Summary of the invention

[0006] The purpose of the present invention is to overcome the above-mentioned problems existing in traditional technologies, and to provide a double-layer composite phase change material capable of photothermal conversion and a preparation method thereof. A double-layer composite phase change material with a photothermal layer and a phase change heat storage layer tightly combined is prepared in a simple and ingenious way. While maintaining a high photothermal conversion efficiency, the amount of photothermal material used is effectively reduced, the preparation is simple, the process repeatability is good, and it is easy to industrialize.

[0007] In order to achieve the above technical objectives and the above technical effects, the present invention is implemented through the following technical solutions:

[0008] The present invention provides a method for preparing a double-layer composite phase change material capable of photothermal conversion, comprising the following steps:

[0009] S1. Mixing expanded graphite and carbon material in a certain mass ratio to obtain mixed powder;

[0010] S2, evenly spreading the composite phase change material powder in the pressing mold as the lower layer, then spreading the mixed powder obtained in step S1 on the composite phase change material powder and covering the entire surface, pressing and molding to obtain a double-layer structure block with the upper layer being the light-to-heat conversion layer and the lower layer being the phase change heat storage layer;

[0011] S3, processing the upper photothermal conversion layer of the double-layer structural block obtained in step S2 to form a certain degree of roughness, thereby obtaining a double-layer composite phase change material capable of photothermal conversion.

[0012] Furthermore, in step S1, the carbon material is carbon nanotubes.

[0013] Furthermore, in step S1, the mass ratio of the expanded graphite to the carbon nanotubes is 1 to 9:1.

[0014] Furthermore, in step S1, the mass ratio of the expanded graphite to the carbon nanotubes is 1.5:1.

[0015] Furthermore, in step S2, the composite phase change material is a paraffin wax / expanded graphite composite phase change material, which is obtained by heating paraffin wax and expanded graphite under vacuum conditions, stirring after the paraffin wax melts, standing under vacuum conditions, and cooling.

[0016] Furthermore, the mass ratio of expanded graphite in the paraffin wax / expanded graphite composite phase change material is 12.5%.

[0017] Furthermore, the expansion ratio of the paraffin wax / expanded graphite composite phase change material is 600 times.

[0018] Furthermore, in step S3, the roughness of the light-to-heat conversion layer is controlled to be 0.01-0.41 mm.

[0019] The beneficial effects of the present invention are:

[0020] The present invention laminates and compresses the photothermal material and the phase change material. Compared with the uniform structure photothermal conversion phase change material and the photothermal conversion phase change microcapsule, the present invention fully utilizes the photothermal material, effectively reduces the amount of photothermal material while maintaining high photothermal conversion efficiency, has simple preparation, good process repeatability, and is easy to industrialize.

[0021] Of course, any product implementing the present invention does not necessarily need to achieve all of the above advantages at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0023] Figure 1 The actual pictures of the double-layer composite phase change material prepared in Example 3 at different angles;

[0024] Among them, a-top view, b-stereoscopic view, c-side view;

[0025] Figure 2 The actual pictures at different angles of the double-layer composite phase change material prepared in Example 3 after 10 photothermal cycles;

[0026] Among them, a-top view, b-stereoscopic view, c-side view;

[0027] Figure 3 The infrared thermal images of Examples 1-5 and Comparative Example 4 are shown;

[0028] Among them, a-Example 1, b-Example 2, c-Example 3, d-Example 4, e-Example 5, f-Comparative Example 4;

[0029] Figure 4 This is a physical diagram of Comparative Example 1;

[0030] Figure 5 This is a physical diagram of Comparative Example 2;

[0031] Figure 6 This is a physical picture of Comparative Example 3. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] The preparation steps of paraffin wax / expanded graphite composite phase change material are as follows: paraffin wax and expanded graphite are heated under vacuum until the paraffin wax melts, stirred for 30 minutes, left to stand for 12 hours under vacuum, and then cooled to obtain the paraffin wax / expanded graphite composite phase change material. Among them, the expanded graphite specification is 360mL / g; the tube diameter of the carbon material is 8-20nm, and the tube length is 5-15um; the particle size of the paraffin wax / expanded graphite composite phase change material powder is 75±25 mesh.

[0034] The specific operation of forming a certain roughness of the light-to-heat conversion layer is to use sandpaper of different meshes (40-2000 mesh) to grind its surface for a certain period of time, and use a roughness meter to detect during the process until the desired roughness is reached.

[0035] The relevant specific embodiments of the present invention are as follows:

[0036] Example 1

[0037] This embodiment provides a double-layer composite phase change material capable of light-to-heat conversion, and the preparation steps are as follows:

[0038] S1. Mix expanded graphite and carbon nanotubes in a mass ratio of 1:1 to obtain a mixed powder.

[0039] S2. Evenly spread 4 g of paraffin wax / expanded graphite composite phase change material powder in a circular pressing mold with an inner diameter of 3 cm as the lower layer, then spread 0.1 g of the mixed powder obtained in step S1 on top of the composite phase change material powder and cover the entire surface, and press into shape to obtain a double-layer structure block with a thickness of 5.5 mm and an upper layer as a light-to-heat conversion layer and a lower layer as a phase change heat storage layer.

[0040] S3, forming the bulk photothermal layer obtained in step S2 with a roughness of 0.15 mm, thereby obtaining the photothermal-convertible double-layer composite phase-change material.

[0041] Example 2

[0042] This embodiment provides a double-layer composite phase change material capable of light-to-heat conversion, and the preparation steps are as follows:

[0043] S1. Mix expanded graphite and carbon nanotubes in a mass ratio of 1.5:1 to obtain a mixed powder.

[0044] S2. Evenly spread 4 g of paraffin wax / expanded graphite composite phase change material powder in a circular pressing mold with an inner diameter of 3 cm as the lower layer, then spread 0.1 g of the mixed powder obtained in step S1 on top of the composite phase change material powder and cover the entire surface, and press into shape to obtain a double-layer structure block with a thickness of 5.5 mm and an upper layer as a light-to-heat conversion layer and a lower layer as a phase change heat storage layer.

[0045] S3, forming the bulk photothermal layer obtained in step S2 with a roughness of 0.15 mm, thereby obtaining the photothermal-convertible double-layer composite phase-change material.

[0046] Example 3

[0047] This embodiment provides a double-layer composite phase change material capable of light-to-heat conversion, and the preparation steps are as follows:

[0048] S1. Mix expanded graphite and carbon nanotubes in a mass ratio of 1.5:1 to obtain a mixed powder.

[0049] S2. Evenly spread 4 g of paraffin wax / expanded graphite composite phase change material powder in a circular pressing mold with an inner diameter of 3 cm as the lower layer, then spread 0.1 g of the mixed powder obtained in step S1 on top of the composite phase change material powder and cover the entire surface, and press into shape to obtain a double-layer structure block with a thickness of 5.5 mm and an upper layer as a light-to-heat conversion layer and a lower layer as a phase change heat storage layer.

[0050] S3, forming the bulk photothermal layer obtained in step S2 with a roughness of 0.41 mm, thereby obtaining the photothermal-convertible double-layer composite phase-change material.

[0051] Example 4

[0052] This embodiment provides a double-layer composite phase change material capable of light-to-heat conversion, and the preparation steps are as follows:

[0053] S1. Mix expanded graphite and carbon nanotubes in a mass ratio of 4:1 to obtain a mixed powder.

[0054] S2. Evenly spread 4 g of paraffin wax / expanded graphite composite phase change material powder in a circular pressing mold with an inner diameter of 3 cm as the lower layer, then spread 0.1 g of the mixed powder obtained in step S1 on top of the composite phase change material powder and cover the entire surface, and press into shape to obtain a double-layer structure block with a thickness of 5.5 mm and an upper layer as a light-to-heat conversion layer and a lower layer as a phase change heat storage layer.

[0055] S3, forming the bulk photothermal layer obtained in step S2 with a roughness of 0.15 mm, thereby obtaining the photothermal-convertible double-layer composite phase-change material.

[0056] Example 5

[0057] This embodiment provides a double-layer composite phase change material capable of light-to-heat conversion, and the preparation steps are as follows:

[0058] S1. Mix expanded graphite and carbon nanotubes in a mass ratio of 9:1 to obtain a mixed powder.

[0059] S2. Evenly spread 4 g of paraffin wax / expanded graphite composite phase change material powder in a circular pressing mold with an inner diameter of 3 cm as the lower layer, then spread 0.1 g of the mixed powder obtained in step S1 on top of the composite phase change material powder and cover the entire surface, and press into shape to obtain a double-layer structure block with a thickness of 5.5 mm and an upper layer as a light-to-heat conversion layer and a lower layer as a phase change heat storage layer.

[0060] S3, forming the bulk photothermal layer obtained in step S2 with a roughness of 0.15 mm, thereby obtaining the photothermal-convertible double-layer composite phase-change material.

[0061] Comparative Example 1

[0062] This comparative example provides a double-layer composite phase change material, and the preparation steps are as follows:

[0063] 4 g of paraffin wax / expanded graphite composite phase change material powder was evenly spread in a circular pressing mold with an inner diameter of 3 cm as the lower layer, and then 0.1 g of carbon nanotubes were spread on top of the composite phase change material powder and covered the entire surface, and pressed into shape to obtain a double-layer composite phase change material with a thickness of 5.5 mm.

[0064] Comparative Example 2

[0065] This comparative example provides a double-layer composite phase change material, and the preparation steps are as follows:

[0066] 4 g of paraffin wax / expanded graphite composite phase change material powder was evenly spread in a circular pressing mold with an inner diameter of 3 cm as the lower layer, and then 0.1 g of surface-modified carbon nanotubes were spread on top of the composite phase change material powder and covered the entire surface, and pressed into shape to obtain a double-layer composite phase change material with a thickness of 5.5 mm.

[0067] Comparative Example 3

[0068] This comparative example provides a double-layer composite phase change material, and the preparation steps are as follows:

[0069] 4 g of paraffin / expanded graphite composite phase change material powder and 0.1 g of carbon nanotubes were evenly spread in a circular pressing mold with an inner diameter of 3 cm, pressed into shape, and the two pressed samples were bonded together using thermal conductive silicone grease to obtain a double-layer composite phase change material with a thickness of 5.6 mm.

[0070] Comparative Example 4

[0071] This comparative example provides a double-layer composite phase change material, and the preparation steps are as follows:

[0072] 4 g of paraffin wax / expanded graphite composite phase change material powder was evenly spread in a circular pressing mold with an inner diameter of 3 cm, and pressed to obtain a composite phase change material with a thickness of 5.4 mm.

[0073] Comparative Examples 1-4 and Examples 1-5 were tested at an intensity of 100 mW / cm 2 The photothermal data of 1h irradiation under simulated sunlight is shown in Table 1:

[0074] Table 1

[0075] Experiment number Peak temperature(℃) Phase change time(s) Photothermal conversion efficiency (%) Comparative Example 1 Sample preparation failed Sample preparation failed Sample preparation failed Comparative Example 2 Sample preparation failed Sample preparation failed Sample preparation failed Comparative Example 3 Sample preparation failed Sample preparation failed Sample preparation failed Comparative Example 4 82.1 915 80.8 Example 1 84.9 875 84.5 Example 2 85.0 870 85.0 Example 3 85.7 845 87.5 Example 4 83.8 890 83.0 Example 5 82.9 905 81.7

[0076] It can be seen from Table 1 that the phase change time of Example 3 is the shortest, and the light-to-heat conversion efficiency and the peak temperature that can be achieved are both the highest, so the sample of Example 3 has the best effect.

[0077] from Figure 4 , Figure 5 , Figure 6 It can be seen that when only carbon nanotubes are used in the upper layer, due to the large difference in surface properties between carbon nanotubes and phase change materials, it is very easy to fall off or stick to the mold, and cannot be combined with the phase change material of the lower layer to form a whole, so a stable double-layer structure cannot be obtained. However, when carbon nanotubes and expanded graphite are mixed evenly at a certain mass ratio and then composited with the phase change material, the expanded graphite that penetrates the upper and lower layers can make the interlayer bond tightly and firmly, while preventing falling off and sticking to the mold, and a double-layer composite phase change material with high light-to-heat conversion ability can be made.

[0078] The phase change latent heat of the double-layer composite phase change material capable of photothermal conversion prepared in Example 1 was tested using a DSC-500B differential scanning calorimeter. The paraffin raw material used was produced by Sinopharm Chemical Reagent Co., Ltd., numbered 69018961, and had a melting point of 48-50°C. The latent heat of melting and solidification of the lower layer paraffin / expanded graphite composite phase change material were 130.61 J / g and 118.21 J / g, respectively, indicating that the prepared double-layer composite phase change material has excellent energy storage performance. A BBZM-I scientific research xenon lamp cold light source was used as a simulated solar light source to test the photothermal conversion performance of the composite phase change material at room temperature. The test conditions were an intensity of 100 mW / cm 2 Irradiate for 1 hour. Use DT-3891G multi-channel temperature measuring instrument and FOTRIC infrared thermal imager to test the temperature of the sample during photothermal conversion. Use 0918 sandblasting roughness tester to test the surface roughness of the sample.

[0079] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing a double-layer composite phase change material capable of photothermal conversion, characterized in that: The steps include: S1. Mixing expanded graphite and carbon material in a certain mass ratio to obtain mixed powder; S2, evenly spreading the composite phase change material powder in the pressing mold as the lower layer, then spreading the mixed powder obtained in step S1 on the composite phase change material powder and covering the entire surface, pressing and molding to obtain a double-layer structure block with the upper layer being the light-to-heat conversion layer and the lower layer being the phase change heat storage layer; S3, processing the upper photothermal conversion layer of the double-layer structural block obtained in step S2 to form a certain degree of roughness, thereby obtaining a double-layer composite phase change material capable of photothermal conversion.

2. The preparation method according to claim 1, characterized in that: In step S1, the carbon material is carbon nanotubes.

3. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of the expanded graphite to the carbon nanotubes is 1 to 9:

1.

4. The preparation method according to claim 3, characterized in that: In step S1, the mass ratio of the expanded graphite to the carbon nanotubes is 1.5:

1.

5. The preparation method according to claim 1, characterized in that: In step S2, the composite phase change material is a paraffin wax / expanded graphite composite phase change material, which is obtained by heating paraffin wax and expanded graphite under vacuum conditions, stirring after the paraffin wax melts, standing under vacuum conditions, and cooling.

6. The preparation method according to claim 5, characterized in that: The mass proportion of expanded graphite in the paraffin wax / expanded graphite composite phase change material is 12.5%.

7. The preparation method according to claim 6, characterized in that: The expansion ratio of the paraffin wax / expanded graphite composite phase change material is 600 times.

8. The preparation method according to claim 1, characterized in that: In step S3, the roughness of the light-to-heat conversion layer is controlled to be 0.01-0.41 mm.